Ibsen on the London stage: Independent theatre as transnational space - Bullock, P (Oxford University Press, 2017)
This article considers the British reception of Ibsen around the turn of the century, replacing modernism’s strongly teleological sense of its own temporality with a more spatially inflected account of artistic production that draws on tropes such as ‘the Republic of Letters’, ‘Weltliteratur’ or recent interest in ‘Global Ibsen’. In particular, it examines the independent theatre movement as an exemplary instance of a transnational space operating outside of national canons and histories, and dependent on the involvement of a large number of individuals whose linguistic and cultural allegiances resist ready definition. It views the contexts of British Ibsen reception around 1900 not from the point of view of their eventual outcome (either in the institutional history of British theatre, or in the story of Ibsen’s eventual place in the literary canon), but as a way of rethinking the interaction between the local, national and international in literary analysis and history.